Achieving water quality standards through the use of total maximum daily loads : developments and challenges - Watkins, Valarie (Air, water and soil pollution science and technology series., 2014)
The Clean Water Act (CWA) contains a number of complex and interrelated elements of overall water quality management. Foremost is the requirement in Section 303 that states establish ambient water quality standards for water bodies, consisting of the designated use or uses of a water body (e.g., recreational, public water supply, or industrial water supply) and the water quality criteria which are necessary to protect the use or uses. Standards are then used to determine which waters must be cleaned up, how much effluent may be discharged, and what is needed for protection. Through permitting,